2008
DOI: 10.1590/s0074-02762008000700010
|View full text |Cite
|
Sign up to set email alerts
|

The redox potential interferes with the expression of laminin binding molecules in Bacteroides fragilis

Abstract: The Bacteroides fragilis ATCC strain was grown in a synthetic media with contrasting redox potential (Eh) levels [reduced (-60 mV) Key words: Bacteroides fragilis -adhesion -redox potential -laminin binding proteins -outer membrane proteinsBacteroides fragilis is a Gram-negative obligate anaerobic bacterium and a common member of the human microbiota (Jousiemies-Somier 2002), but it is also an important opportunistic pathogen. This bacterium is the most frequently isolated anaerobic species from human intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…It was later found that both Rck and a similar protein, PagC, are able to bind laminin, and their expression in Escherichia coli confers the capacity for adherence to basement membranes and host cells (11). Adherence to ECM is also believed to contribute to virulence of Bacteroides fragilis, Borrelia burgdorferi, Haemophilus influenzae, and Moraxella catarrhalis (6,18,19,53). Thus, it would not be surprising for ECM adherence by H. pylori to influence persistence or pathogenesis.…”
mentioning
confidence: 99%
“…It was later found that both Rck and a similar protein, PagC, are able to bind laminin, and their expression in Escherichia coli confers the capacity for adherence to basement membranes and host cells (11). Adherence to ECM is also believed to contribute to virulence of Bacteroides fragilis, Borrelia burgdorferi, Haemophilus influenzae, and Moraxella catarrhalis (6,18,19,53). Thus, it would not be surprising for ECM adherence by H. pylori to influence persistence or pathogenesis.…”
mentioning
confidence: 99%